Clinical management of pneumonic pasteurellosis in boer kids: a case report - Lim, Eric Teik Chung; Abdullah, Faez Firdaus Jesse; Abba, Yusuf; Tijjani, Abdulnasir; Sadiq, Muhammad Abubakar; Mohammed, Konto; Osman, Abdinasir Yusuf; Adamu, Lawan; Mohd Lila, Mohd Azmi; Haron, Abdul Wahid (Academic and Scientific Publishing, 2015)
Pneumonic pasteurellosis caused by Mannhaemia haemolytica (M. haemolytica) is a common disease with high prevalence in sheep and goats. This clinical case reports the occurrence of pneumonic pasteurellosis in two of Boer-crossed kids. Two Boer-crossed kids age 1-week old, were presented with complain of in appetence and weakness. The farm had previous history of sudden death among the kids. Clinical examination findings revealed that the kids were having harsh lung sound with present of bilateral serous nasal discharges. Nasal swabs and fecal samples were collected as diagnostic work-ups and both kids were diagnosed with pasteurellosis. The kids were treated with dextrose fluid, penicillinstreptomycin antibiotic and flunixin meglumine non-steroidal anti-inflammatory drug. After third day of hospitalization, both kids showed positive response to the treatments. The prognosis of this case was good where accurate and prompt treatment were able to resolve the case.